A Four Factor Model for the Selection of a Systems Development Approach - Dececchi, Thomas (My University, 1989)
The purpose of this research was to develop a model which would aid in selecting the best systems development approach for supplying a decision maker with a computer based support system. The research proceeded in several stages. First a hierarchical model was developed. The "top" level of the model described situations in terms of four factors or meta-constructs; User Participation in the Decision Making Process, Problem Space Complexity, Resource Availability and Organizational Context. The set of factors was based on Churchman's systems theory and the organizational interaction represented by the Leavitt Diamond. In the "lower" level the factors were each described by a set of attributes. The list of attributes was based on a literature search, aided by a model developed by Ginzberg and Stohr. Next the model was validated in a three phase process. The first phase involved validation of the model structure and content. A normative group technique (Delphi method) was chosen to obtain expert consensus on both the factors and the attributes that defined them. The second phase of the validation aided in content validation of the lower level of the model and associated a factor value with each unique set of attribute levels. It consisted of two sets of case-based interviews. Two of the factors had been defined as managerial in nature and these interviews were conducted with senior administrative personnel. The other two factors had been defined as technical in nature and the subjects of these interviews had a systems background. The thrid phase of the research aided in content validation of the "top" level of the model and determined which approaches were preferred in which situations (unique set of factor values). It consisted of a set of case-based interviews with senior MIS personnel (including experienced academics) to assign the "best" or "preferred" approach to each of the situations (set of factor values). Based on the results of these studies we have shown that it is possible to define situations in terms of a hierarchically ordered set of attributes, for the purpose of determining how best to provide computer based support for the decision maker facing a particular situation.
Keywords: Computer Engineering; Computer Engineering